Hedging, speculation, and investment in balance-sheet triggered currency crises - Andreas Röthig; Willi Semmler; Peter Flaschel (Technische Universität Darmstadt, Department of Law and Economics, 2006)
This paper explores the linkage between corporate risk management strategies, investment, and economic stability in an open economy with a flexible exchange rate regime. Firms use currency futures contracts to manage their exchange rate exposure - caused by balance sheet effects as in Krugman (2000) - and therefore their investments' sensitivity to currency risk. We find that, depending on whether futures contracts are used for risk reduction (i.e., hedging) or risk taking (i.e., speculation), the implied magnitudes of recessions and booms are decreased or increased. Corporate risk management can therefore substantially affect economic stability on the macrolevel.
Keywords: E32; E44; F31; F41; 330; Mundell-Fleming-Tobin model; foreign-debt financed investment; currency crises; real crises; currency futures; hedging; speculation; Hedging; Währungskrise; Risikomanagement; Flexibler Wechselkurs; Theorie